Borobudur’s Changing Cultural Landscape and Genius Loci - Katarina Mladenović (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
Cultural landscape is produced socially trough space and time. Cultural landscape also refers to cultural heritage that is only focused on the cultural object but also on a wider context where it is placed. This is a qualitative descriptive study which observes historical data through the conceptual framework of genius loci. Data is collected through bibliography study with the focus on how political institutions observed and built the environmental image of the place. Political institutions define how the relationship between the natural and human-made environment is sought to exist. Worldviews that have changed from the inception of Borobudur cultural landscape to the present day were influencing ongoing shifts of values, beliefs and cultural relationship towards the place.